Compact corrugatеd horn antenna initial design for microwave diagnostics in Uragan-2M stellarator - Pavlichenko, R.O.; Pavlichenko, N.I. (Problems of Atomic Science and Technology, 2023)
In this paper, a well-known design procedure is proposed for the design of wideband constant-beam width conical corrugated horn antennas, with minimum design and construction complexity. The inputs to the procedure are the operating frequency band, the required minimum beam width in the entire frequency band, and the frequency in which the maximum gain is desired to occur. Based on these values, the procedure gives a relatively good design with a relative bandwidth of up to 2.1:1 Based on the proposed procedure, a corrugated horn antenna with a constant beam width over the frequencies of 10 to 14 GHz was designed and simulated using commercial software. This paper presents initial design for the development of quasi-optical corrugated conical horn for reflectometry diagnostics for the Uragan-2M stellarator plasma experiments. Пропонується відома методика проектування широкосмугових конічних гофрованих рупорних антен з постійною шириною діаграми спрямованості яка має мінімальну складність проектування і побудови Вхідними даними для процедури є робоча смуга частот необхідна мінімальна ширина променю у всій смузі частот і частота на якій бажано досягти максимального коефіцієнта підсилення На основі цих значень процедура дає відносно хорошу конструкцію з відносною шириною смуги пропускання до 2.1:1 На основі запропонованої методики було спроектовано і змодельовано за допомогою комерційного програмного забезпечення гофровану рупорну антену з постійною шириною смуги пропускання у діапазоні частот від 10 до 14 ГГц У статті представлено початковий проект розробки квазіоптичної гофрованої конічної рупорної антени для рефлектометричної діагностики для плазмових експериментів стеларатора Ураган-2М.